Effects of Dexmedetomidine on Postoperative Nausea and Vomiting in Adult Patients Undergoing Ambulatory Thyroidectomy: A Randomized Clinical Trial - Xie, Cuiyu; Zhang, Caihui; Sun, Hao; Lu, Yao (Frontiers in Medicine, 2021)
Background: Postoperative nausea and vomiting (PONV) is a common and disturbing problem in patients undergoing ambulatory thyroidectomy. This prospective trial aimed to explore whether dexmedetomidine (DEX) combined with azasetron (AZA) can further drop the incidence of PONV in patients undergoing ambulatory thyroidectomy compared with AZA. Methods: This single-center, randomized, double-blind trial involved 172 adult patients undergoing ambulatory thyroidectomy. The individuals were randomized to DEX + AZA group and AZA group. In the DEX + AZA group, patients received dexmedetomidine 0.5 μg kg−1 for 10 min and then the infusion rate was held at 0.1 μg kg−1 h−1 until the completion of the operation, while the same amount of 0.9% saline in the AZA group. At the completion of the surgery, 10 mg azasetron was administered to every patient in both groups. The primary outcome was the incidence of 24 h PONV after ambulatory thyroidectomy. The secondary outcomes included residence time in recovery room, pain scores, severity of nausea, and adverse events. Results: No significant difference was found in the incidence of 24-h PONV between the DEX + AZA group and the AZA group [36% (30 of 84) vs. 38% (32 of 84); relative risk, 0.94; 95% confidence interval (CI), 0.63–1.40; P = 0.749]. The incidence of severe nausea was similar between the DEX + AZA group and the AZA group [57% (12 of 21) vs. 43% (9 of 21); relative risk, 1.33; 95% CI, 0.72–2.50; P = 0.355]. Conclusions: Intraoperative dexmedetomidine combined with azasetron failed to drop the incidence of 24-h PONV compared with azasetron alone in patients undergoing ambulatory thyroidectomy.